Sequencing and comparative genome analysis of streptococcus sanguinis and streptococcus gordonii / Zheng Wenning - Zheng, Wenning (2017)
Mitis group oral streptococci are opportunistic human pathogens that live primarily in the oral cavity, and potentially cause infective endocarditis (IE) in neutropenic patients with haematological disease. Among the members of Mitis group, Streptococcus sanguinis and Streptococcus gordonii are two pioneer colonizing species of dental plaque that are often associated with streptococcal IE infection. In this study, comparative genome analyses of these two closely-related species were performed in order to provide a better understanding of the co-existence of S. gordonii and S. sanguinis and their biology, evolution, genomics and virulence in invasive infections. Here I have successfully sequenced, assembled, identified and annotated 27 strains of 6 species of Mitis group oral streptococci that were isolated from patients in different geographical areas. A comparative whole-genome study was performed on 14 S. gordonii strains and 5 S. sanguinis strains along with the reference strains of S. gordonii Challis and S. sanguinis SK36 using different bioinformatics approaches such as phylogenetic analysis, functional enrichment analysis, orthologous genes and pan-genome analysis, comparative pathogenomics analysis, comparative prophage analysis and genomic island (GI) analysis. The data showed that both species have generally high sequence homology with evidence of their considerable number of core genes and virulence genes. Significantly, S. sanguinis carries genes involved in nickel, cobalt and cobalamin utilization in their core genomes. Interestingly, both S. sanguinis and S. gordonii harbour open pan-genomes, indicating their potential in exhibiting greater virulence by acquiring antibiotic resistance and new virulence genes in the future. While S. gordonii has been found to recruit additional copies of ComCDE quorum-sensing system as competence mechanism to support its virulence, S. sanguinis has acquired a broad array of potential antibiotic resistance genes including the drug/metabolite transporter (DMT) superfamily, rsmE, TetR/AcrR family transcriptional regulator (TFR) and GNAT acetyltransferase through horizontally-transferred GIs to further support its bacterial adaptation in the host cells during infections. To facilitate the expanding Streptococcus genus research worldwide, I developed a Mitis group oral streptococci genomic resource and analysis platform, StreptoBase (http://streptococcus.um.edu.my), allowing researchers to access and browse the comprehensive Streptococcus genomes and annotations. It currently hosts 104 Mitis group genomes including 27 strains which were sequenced using the high-throughput Illumina HiSeq technology platform, enabling comparative analyses and visualization of both cross-species and cross-strain characteristics of Mitis group bacteria. StreptoBase incorporates sophisticated in-house designed bioinformatics web tools such as Pairwise Genome Comparison (PGC) tool and Pathogenomic Profiling Tool (PathoProT), which facilitate comparative pathogenomics analysis of Streptococcus strains. In conclusion, this comparative genome study has successfully characterised the core genomes of S. sanguinis and S. gordonii, and identified key differences between the species. These new insights into the genomic differences, biology and virulence of the two closely-related species will provide a foundation for further investigations into how these bacteria make the transition from oral commensal species into important pathogens in IE. Ultimately, this may lead to improved measures for dental plaque control and/or better management of diseases caused by these opportunistic pathogens. With addition of new genome sequences of S. sanguinis and S. gordonii in StreptoBase, it will be an invaluable platform to accelerate Mitis group streptococci research in their impact on human health and disease.